2016
DOI: 10.1007/s11046-016-0026-3
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Diversity of Malassezia pachydermatis from Healthy and Diseased Domestic Animals

Abstract: Malassezia pachydermatis is part of the normal cutaneous microbiota of wild and domestic carnivores. However, under certain conditions this yeast can overproliferate and cause several diseases in its host, mainly otitis and dermatitis in dogs. The aim of this study was to conduct a molecular characterization of M. pachydermatis isolates from healthy and diseased domestic animals, in order to assess the molecular diversity and phylogenetic relationship within this species. The large subunit (LSU) and the intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 29 publications
5
30
0
Order By: Relevance
“…Due to the genetic diversity observed in M . pachydermatis strains [18, 3032], we also hypothesize that the same could happen within this species.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Due to the genetic diversity observed in M . pachydermatis strains [18, 3032], we also hypothesize that the same could happen within this species.…”
Section: Discussionmentioning
confidence: 92%
“…pachydermatis genotypes and the new ITS and beta-tubulin genotypes from these lipid-dependent strains did not exceed the variation generally observed to occur in M . pachydermatis [18]. Besides, in the phylogenetic tree of the LSU rRNA sequences, the lipid-dependent strains were grouped and interspersed with the non-lipid dependent M .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amplification of the chitin synthase 2 ( CHS2 ) gene in seven Malassezia species yielded an ~620 bp fragment with 95% sequence homology between the species, although phylogenetic analyses indicated that each species was genetically distinct . Limited genetic variability in seen in the CHS2 gene amongst M. pachydermatis isolates from dogs in previous studies, although wider variation was observed in another study . Partial sequencing of the ß‐tubulin gene in Malassezia provides a further opportunity for species and genotype differentiation …”
Section: Diagnostic Methods: Molecular and Mass Spectrometry Identifimentioning
confidence: 94%
“…Genotypic approaches involving analyses of sequences obtained from multiple loci on the Malassezia genome, such as combined analyses of D1/D2, ITS, CHS2 and ß‐tubulin sequences, has proven to be a powerful tool in the epidemiological assessment of the intraspecific variations and adaptation of these particular genotypes to specific hosts …”
Section: Diagnostic Methods: Molecular and Mass Spectrometry Identifimentioning
confidence: 99%